A retrospective study of stage IB node-negative cervical cancer treated with adjuvant radiation with standard pelvic versus central small pelvic fields. Issue 1 (2nd January 2018) - Ralefala, Tlotlo B; van Wijk, Leon; Saidu, Rakiya
Abstract : Objective: To compare two types of postoperative radiation therapy (PORT) in early-stage, node-negative cervical cancer treated at Groote Schuur Hospital, Cape Town, South Africa. Materials and methods: A retrospective observational study of patients with stage IB cervical cancer treated with radical surgery between 1984 and 2010. Node-negative patients regarded as at risk of pelvic recurrence received PORT, with or without concurrent cisplatin or additional vaginal brachytherapy. The PORT was given with either whole pelvis fields (WPF), or with central small pelvic fields (SPF). Data concerning indications for adjuvant therapy, treatment outcomes and grade 3–4 treatment-related toxicities, including leg lymphoedema, were extracted from clinical records. Results: Thirty-one patients received WPF, and 56 SPF. The overall 5-year survival rate was 85%. No significant differences in survival rates were found between the WPF and SPF groups (log rank p = 0.67). Relapse patterns and the crude grade 3–4 treatment morbidity rates did not differ, although two patients in the WPF group (6%) died of treatment-related complications. Conclusions: The expected benefit of PORT with SPF, which targets the cervical tumour bed and para-cervical tissues only, is a reduction in small bowel morbidity and lymphoedema. It is not possible to ascertain from this audit whether the SPF technique reduces complications, or that it increases out-of-field pelvic relapses. It seems unlikely that a randomised controlled trial will ever be performed, as a large sample size would be required. Comparisons of pooled SPF data with historical WPF controls seem the best option to establish the safety of this approach.